Development of QIRAMA Website-Based Media for Teaching Arabic Reading Skills to Eighth-Grade MTs Students in Batang - Atikah Junelsya; Zukhaira; Mushaffa Rasyid Ridha (Alsina : Journal of Arabic Studies, 2026)
The reading skill (mahārah qirāʾah) is one of the four language skills that play an important role in Arabic language learning. However, research findings indicate that Arabic reading instruction for eighth-grade students at MTs in Kota Batang remains dominated by conventional teaching methods, leading to low student interest and motivation, as well as limited ability to comprehend Arabic texts. Based on these problems, this study aims to develop a web-based learning media, QIRAMA (Qirāʾah Mudah dan Asyik), to support Arabic reading skills among eighth-grade MTs students in Kota Batang. The development model used in this study is the Hannafin and Peck model, consisting of three main stages: needs assessment, design, development, and implementation. QIRAMA was designed and developed by integrating reading materials, audio features, supporting visuals, and interactive exercises. The validation results from media, material, and language experts yielded an average score of 4.72, indicating high feasibility. These findings indicate that QIRAMA is feasible based on expert validation and ready for trial as an interactive website-based learning medium for Arabic reading skills for Grade VIII MTs students in Batang City. This study focuses on feasibility only, with classroom trials suggested as the next step.